Peningkatan Trust Berbelanja Online pada Mahasiswa Perguruan Tinggi di Wilayah Bandung Berbasis Information Privacy Concern Dan Privacy Policy - Windiarti, Sofia; Putra, Vicky Dzaky Cahaya (J-MAS (Jurnal Manajemen dan Sains), 2024)
Before entering the era of online shopping, previously information systems were only intended for internal company parties such as company employees. In this era of artificial intelligence, accounting information systems are also operated by consumers. Consumers operate information systems to be able to complete purchases of goods or services online. Based on research results through mass media, it is known that consumers' current shopping tendencies are more towards shopping online. The reason consumers tend to prefer shopping online is because the prices offered by online companies are cheaper and they save time shopping. When consumers make online shopping transactions, concerns arise about sharing personal data with e-commerce companies. These concerns include the use of consumers' personal data by e-commerce companies. This research is descriptive verification research using a survey approach. This research is classified as quantitative research. The respondents who will be studied in this research are students spread across universities in the city of Bandung. The data analysis method uses SEM-PLS. The results of the research show that information privacy concerns have a significant negative influence on trust, privacy policy has a significant positive influence on trust and simultaneously information privacy concerns and privacy policy have a significant positive influence on trust. So it can be concluded that if there is an increase in information privacy concerns and privacy policies, it will have an impact on increasing trust in online shopping for university students in the Bandung City area.